KESEHATAN BANK TERHADAP PERTUMBUHAN LABA PADA BANK TABUNGAN PENSIUN NASIONAL SYARIAH PERIODE 2014-2021 - Mauliddia, Noer Cholifa; Suryani; Saraswati, Henny (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
The Financial Services Authority noted that one of the of Sharia Commercial Banks that experienced a decline in profit was the Bank Tabungan Pensiun Nasional Syariah, which experienced a decrease in profit in 2020, which was minus 38.9%. This study aims to determine the effect of the NPF, FDR, ROA, NI and CAR to profit growth at the Bank Tabungan Pensiun Nasional Syariah. The population in this study were 15 Bank Umum Syariah and purposive sampling technique, 1sample was obtained which was used in this study. The analysis technique used is descriptive statistics, classical assumption test: normality, multicollinearity, heteroscedasticity, and autocorrelation, multiple regression analysis, correlation coefficient test (r), coefficient of determination test (adjusted r square), f test (simultaneous) and t test (Partial). The results showed that NPF, FDR, ROA, and NI partially had no effect on profit growth, while CAR had a partial effect on profit growth. Simultaneously all variables affect profit growth. The predictive ability of these five variables on profit growth is 64.8% while the remaining 35.2% is influenced by other variables outside the regression model.